The metaphysics of free will : an essay on control - Fischer, John Martin (Blackwell, 1994)
In this text, Fischer argues that although we naturally assume that we have control of our behaviour and are morally responsible agents, the assumption that we have this sort of control can be called into question. Arguments can be made that if, say, causal determinism obtains or God exists, we lack this sort of control. And it is not absolutely evident that causal determinism is false and God does not exist. Thus, some of the most important and fundamental features of our lives can be put in doubt. Fischer attempts to protect us from these skeptical doubts by setting out new arguments about the nature of free will and control. His view suggests that we can be confident of our moral responsibility and personhood even if causal determinism turned out to be true or God were to exist.